Therapeutic effect of fecal microbiota transplantation on chronic unpredictable mild stress-induced depression - Cai, Ting; Zheng, Shao-peng; Shi, Xiao; Yuan, Ling-zhi; Hu, Hai; Zhou, Bai; Xiao, Shi-lang; Wang, Fen (Frontiers in Cellular and Infection Microbiology, 2022)
Background and objective: Depression is a complex neuropsychiatric disease with extensive morbidity. Its pathogenesis remains unclear, and it is associated with extremely low rates of cure and complete remission. It is vital to study the pathogenesis of depression to develop effective treatments. This study aimed to explore the therapeutic effects and mechanisms of fecal microbiota transplantation (FMT) for the treatment of depression in rats. Methods: Thirty Sprague-Dawley (SD) rats were randomly divided into three groups: control, chronic unpredictable mild stress (CUMS) to model depression, and CUMS+FMT. For the CUMS and CUMS+FMT groups, after CUMS intervention (four weeks), the rats were given normal saline or FMT (once/week for three weeks), respectively. Behavior, colonic motility, 16S rDNA amplicon sequencing, and untargeted metabolomics on fecal samples were compared between the three rat groups. The following markers were analyzed: 5-hydroxytryptamine (5-HT), gamma-aminobutyric acid (GABA), glutamate (Glu), and brain-derived neurotrophic factor (BDNF) levels in the hippocampus; glucagon-like peptide 1 (GLP-1), lipopolysaccharide (LPS), and interleukin (IL)-6 levels in the serum; and GLP-1, GLP-1 receptor (GLP-1R), and serotonin 4 receptor (5-HT4R) levels in colonic tissues. Results: FMT improved symptoms of depression and colonic motility in rats exposed to CUMS. The expression levels of 5-HT, GABA, BDNF, and other biochemical indices, significantly differed among the three groups. Meanwhile, the intestinal microbiota in the CUMS+FMT group was more similar to that of the control group with a total of 13 different fecal metabolites. Conclusion: FMT exerted antidepressant effects on CUMS-induced depression in rats, and the mechanism involved various neurotransmitters, inflammatory factors, neurotrophic factors, and glucagon-like peptides.